ANALISIS POSTUR KERJA PADA SAAT MENGGANTI OLI MOBIL DENGAN MENGGUNAKAN METODE RAPID UPPER LIMB ASSESSMENT (RULA) DAN RAPID ENTIRE BODY ASSESSMENT (REBA) DI BENGKEL BAROKAH MANDIRI - Nurul Hudaningsih; Didi Rahman; Iwan Ahmad Jumari; Fazriansyah (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2021)
This research provides benefits to the Mandiri Barokah Workshop to produce good quality workers in terms of ergonomics. Ergonomics is the study of human relations with all the facilities found in the workplace with the aim of getting the maximum quality of work results. Ergonomics is synonymous with a harmonious relationship between humans, work facilities (tools or machines) and the work environment. This harmonious relationship causes humans to pay attention to good work posture in order to prevent all the worst that can happen, such as injury and exposure to disease. In addition to being beneficial for workers and the surrounding environment, work posture regulation is also beneficial in increasing productivity, such as increasing the level of concentration and accuracy in work. The methods used in this study are the Rapid Upper Limb Assessment (RULA) and the Rapid Entire Body Assessment (REBA). The RULA method evaluates posture, strength and muscle activity that causes injury due to repetitive activities to detect risky work postures and make improvements as soon as possible. . Meanwhile the REBA method can be used to quickly assess the work position or posture of an operator's neck, back, wrists and feet. REBA did not take a long time to complete and perform a general score on the list of activities indicating the need to reduce the risk caused by the operator's work posture. Through these two methods, it will be observed that different work attitudes will produce different strengths. When working, posture should be done scientifically so that it can minimize musculoskeletal growth.